The playbook : 52 rules to aim, shoot, and score in this game called life - Alexander, Kwame (Houghton Mifflin Harcourt, 2017)
"Kwame Alexander shares poetry and inspiring lessons about the rules of life, as well as uplifting quotes from athletes such as Stephen Curry and Venus Williams and other exemplars like Sonia Sotomayor and Michelle Obama in this motivational and inspirational book just right for graduates of any age and anyone needing a little encouragement"--